Decolorisation of batik waste water by Marasmiellus palmivorus using modified fixed bed reactor - Kardena, Edwan; A.N.K., Pratama; S.H., Suhardi; K., Hasan; A.J., Effendi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Batik waste water is dominated by textile dyes that are recalcitrant, hydrophobic, and molecular complexes. Azo, Nitroso, Azine, and Thiazolesare are among synthetic dyes used in batik industry. One of the well known white root fungus species that is able to degrade such dyes is Marasmiellus palmivorus. It has the ability to produce various enzymes such as manganese peroxidase, lignin peroxidase and laccase. Laccase (EC 1.10.3.2) catalyzes wide variety of aromatic hydrogen oxidation by reduction of oxygen and water. This research was conducted using two types of azo dye coloring agents, namely Levafix blue E-RA gran and Telon Red. This study was performed using optimized age of Solid State Fermentation (SSF), which was then inserted into a modified fixed bed reactor for 4 hours. Reduction of the color was observed every 15 minutes and the substrate used for growth of fungus was sawdust. The experiments demonstrated that crude enzyme of MarasmiellusSSF had activity of 97.8 U/L using ABTS reagent at 22-day of age bag log incubation. The total protein content, which was measured using the Bradford reagent, peaked at 154 mg/L on the 10th day. Such results indicated the great potential of utilizing Marasmiellus-SSF in modified fixed bad reactor to treat batik waste water.